Self-efficacy Anak yang Berhadapan dengan Hukum di Lembaga Pembinaan Khusus Anak - Ibad, Muhammad Irsyadul; Naqliyah, Najlatun; Hariastuti, Retno Tri (Program Studi Bimbingan dan Konseling Islam, 2024)
A child who becomes a perpetrator, witness, and victim of violence can often be harmed in material and immaterial ways, including emotional shock, emotional stability, and psychological disorders. The purpose of this coaching program is to help children avoid repeating their mistakes, regain their self-confidence, and re-enter society as accepted members. Self-efficacy plays a significant role in the arrangement process by motivating children to make positive changes during the foster period. This study employs a qualitative research approach, utilizing a field study model. This study examines the Self-efficacy of children in conflict with the law. The Class I Blitar Special Child Development Institution serves as the chosen research location in this case. The study's results demonstrated the Self-efficacy of children in conflict with the law through the restoration of their self-confidence during the foster period. The Self-efficacy that foster children actually possess is not solely due to their coaching, but also to the influence of their peers and environment. When they study under guidance in a semi-boarding school environment, they feel they get support from various parties in dealing with the legal problems that befall them.